A VALUABLE NATURAL AREA AS A SYSTEM MARKETING PRODUCT VERSUS EXPECTATIONS OF TOURISTS AS ACTIVE PURCHASERS - Baruk, Agnieszka; Goliszek, Anna (Acta Scientiarum Polonorum. Oeconomia, 2019)
The article is theoretical and empirical in nature. The theoretical part provides a cognitive and critical analysis of the world literature. According to the approach presented in this part, valuable natural areas are ‘system marketing products’ which should be co-created by purchasers. The research aim of the article is to identify the significance assigned by tourists to various characteristics of valuable natural areas and group the tourists based on this. Three research questions were formed. In order to answer them, primary research was conducted by means of a questionnaire. The results were statistically analysed using the method of averaging and factor analysis. The results indicate that the relatively highest significance from the 25 elements of valuable natural areas evaluated was assigned to cleanliness and food. Untypical elements (e.g. ‘photographic safari’) were the least significant. Respondents were assigned to six groups linked to various types of activities. This points to the necessity to adapt elements of the product, i.e. a valuable natural area, to the various expectations of the purchasers.